Molecularly imprinted electrochemical sensor based on magnetic porous carbon material as well as preparation method and application of molecularly imprinted electrochemical sensor

By using a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials, the problem of recognition sites being located inside polymers in existing technologies has been solved, achieving efficient PFOA detection, improving the sensor's sensitivity and selectivity, and simplifying the preparation process.

CN120847202APending Publication Date: 2025-10-28SHAANXI UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510995094.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

In existing surface molecularly imprinted electrochemical sensors used for PFOA monitoring, the recognition sites are mostly located inside the polymer, resulting in low mass transfer efficiency and hindering elution and adsorption. This severely limits the rapid binding of target molecules and greatly reduces the sensor's detection sensitivity.

Method used

A molecularly imprinted electrochemical sensor based on magnetic porous carbon materials was developed. This involved preparing Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure, and introducing KH570 onto its surface. The resulting material underwent free radical polymerization and was combined with a Co3O4@Ag composite material to modify the electrode, forming a magnetic surface molecularly imprinted polymer that improved the uniformity of recognition site distribution and mass transfer rate.

Benefits of technology

It significantly improves the detection sensitivity and selectivity of the sensor, simplifies the preparation process of imprinted polymer materials, improves the preparation efficiency of materials, and enables rapid separation under the action of an external magnetic field, reducing the separation difficulty and enhancing the recognition efficiency and anti-interference ability of PFOA.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120847202A_ABST
    Figure CN120847202A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of molecularly imprinted polymers, and discloses a molecularly imprinted electrochemical sensor based on a magnetic porous carbon material as well as a preparation method and application thereof, and the preparation method comprises the following steps: introducing KH570 to the surface of a magnetic porous carbon material Fe3O4 (at) PCS with a core-shell structure to obtain a KH570 modified magnetic porous carbon material Fe3O4 (at) PCS-KH570, and carrying out a free radical polymerization reaction to obtain the magnetic porous carbon material Fe3O4 (at) PCS-KH570 modified magnetic porous carbon material Fe3O4 (at) PCS-KH570. A magnetic surface molecularly imprinted polymer Fe3O4 (at) PCS (at) MIP is obtained; the surface of a preset electrode is modified with a Fe3O4 (at) PCS (at) MIP and Co3O4 (at) Ag composite material, and the molecularly imprinted electrochemical sensor based on the magnetic porous carbon material is obtained. The prepared molecularly imprinted electrochemical sensor based on the magnetic porous carbon material has the characteristics of small separation and recovery difficulty, high recognition efficiency and short detection period, and has relatively good selectivity, anti-interference performance and stability on PFOA (perfluorooctanoic acid).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of molecularly imprinted polymer technology, and specifically relates to a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials, its preparation method, and its application. Background Technology

[0002] Perfluorooctanoic acid (PFOA) is a synthetic organic compound that is widely used in industrial production and other fields due to its excellent properties. However, it has also attracted much attention due to its environmental persistence and potential health risks. Therefore, monitoring PFOA is a key step in assessing its environmental distribution, pollution level and health risks.

[0003] Currently, traditional methods for PFOA monitoring include high-performance liquid chromatography (HPLC), mass spectrometry (MS), and gas chromatography (GC). However, these traditional methods generally require cumbersome pretreatment steps and have high costs, which greatly limits their application in PFOA detection. With the development of surface molecular imprinting (SMIT) technology, surface molecular imprinted electrochemical sensors constructed by combining electrochemical detection and SMIT technology can overcome the limitations of the above traditional methods and have the advantages of simple detection procedures, fast response speed, low cost, and high selectivity.

[0004] However, existing surface molecularly imprinted electrochemical sensors for PFOA monitoring are generally prepared using electropolymerization methods such as bulk polymerization or precipitation polymerization. Examples include Chinese patent applications "A perfluorooctanoic acid electrochemical sensor based on molecular imprinting and aptamer dual recognition and its construction method and application" (publication number CN118671155A), "A perfluorooctanoic acid anti-interference electrochemical molecularly imprinted sensor and its preparation method and application" (publication number CN118533933A), and "Fluorophilic and hydrophobic functional monomers and their synthesis methods and applications, detection electrodes and their preparation methods" (publication number CN119552106A). Existing surface molecularly imprinted electrochemical sensors prepared by electropolymerization methods have limited monomer types and poor designability. Furthermore, the recognition sites of the imprinted polymers prepared by electropolymerization methods are mostly located inside the polymer, resulting in low mass transfer efficiency and hindering elution and adsorption. This severely limits the rapid binding of target molecules, greatly reduces the detection sensitivity of the sensor, and consequently seriously affects the monitoring accuracy of PFOA. Summary of the Invention

[0005] To address the technical problems existing in the prior art, this invention provides a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials, its preparation method, and its application. This solves the technical problem that the recognition sites of surface molecularly imprinted electrochemical sensors used for PFOA monitoring are mostly located inside the polymer, resulting in low mass transfer efficiency and hindering elution and adsorption. This severely limits the rapid binding of target molecules and greatly reduces the detection sensitivity of the sensor.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] This invention provides a method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials, comprising:

[0008] Preparation of Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure;

[0009] KH570 was introduced onto the surface of the magnetic porous carbon material Fe3O4@PCS with a core-shell structure to obtain KH570 modified magnetic porous carbon material Fe3O4@PCS-KH570;

[0010] Free radical polymerization was carried out on the surface of KH570 modified magnetic porous carbon material Fe3O4@PCS-KH570 to obtain magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP;

[0011] By modifying the surface of a pre-defined electrode with magnetic surface molecularly imprinted polymers Fe3O4@PCS@MIP and Co3O4@Ag composite materials, a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials is obtained.

[0012] Furthermore, the process for preparing Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure, includes:

[0013] Fe3O4-NH2 magnetic nanoparticles were prepared using a solvothermal method.

[0014] Using Fe3O4-NH2 magnetic nanoparticles as the magnetic core, a melamine-formaldehyde MF resin shell was prepared on the outside of the Fe3O4-NH2 magnetic nanoparticles using the F127-TMB soft template method to obtain Fe3O4@MF.

[0015] Fe3O4@MF was carbonized to obtain Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure.

[0016] Furthermore, the process of introducing KH570 onto the surface of the core-shell structured magnetic porous carbon material Fe3O4@PCS to obtain KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570 is as follows:

[0017] Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure, was ultrasonically dispersed in an ethanol solution. KH570 was added and stirred until homogeneous. The mixture was then heated in a water bath to react. After the reaction, the mixture was magnetically separated, washed, and vacuum dried to obtain the KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570.

[0018] Furthermore, the process of obtaining the magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP by performing free radical polymerization on the KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570 includes:

[0019] Using KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570 as a polymerization support, template molecules, functional monomers, crosslinking agents and initiators were added to carry out free radical polymerization to obtain the polymerization product.

[0020] The template molecules in the polymerization product were removed by Soxhlet extraction to obtain the magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP.

[0021] Furthermore, the template molecule is perfluorooctanoic acid, the functional monomers are acrylamide and 2-trifluoromethacrylic acid, the crosslinking agent is ethylene glycol dimethacrylate, and the initiator is azobisisobutyronitrile.

[0022] Furthermore, the preparation process of the Co3O4@Ag composite material includes:

[0023] ZIF-67MOF material was calcined under a nitrogen atmosphere to obtain Co3O4 material;

[0024] Co3O4 material was ultrasonically dispersed in deionized water, AgNO3 aqueous solution was added and mechanically stirred, and then NaBH4 solution was added dropwise under an ice-water bath to carry out the reaction. After the reaction was completed, the Co3O4@Ag composite material was obtained by centrifugation, washing and vacuum drying.

[0025] Furthermore, the preparation process of ZIF-67MOF material includes:

[0026] A methanol solution of Co(NO3)2·6H2O and a methanol solution of 2-methylimidazole were mixed and stirred, and then allowed to stand for aging. After aging, the ZIF-67MOF material was obtained by centrifugation, washing and vacuum drying.

[0027] Furthermore, the process of modifying the surface of a pre-defined electrode with magnetic surface molecularly imprinted polymers Fe3O4@PCS@MIP and Co3O4@Ag composite materials to obtain a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials is as follows:

[0028] The Co3O4@Ag composite material was dispersed in ultrapure water to obtain dispersion system A;

[0029] The magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP was dispersed in ultrapure water to obtain dispersion system B;

[0030] The dispersion system A and the dispersion system B were sequentially drop-coated onto the surface of a preset electrode, and after drying, a molecularly imprinted electrochemical sensor based on magnetic porous carbon material was obtained.

[0031] The present invention also provides a molecularly imprinted electrochemical sensor based on magnetic porous carbon material, which is prepared by the aforementioned method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon material.

[0032] This invention also provides an application of a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials, which is used to identify and detect perfluorooctanoic acid in an environmental system.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0034] This invention provides a method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials. This method combines magnetic core-shell nanoparticles, surface molecular imprinting technology, and electrochemical detection, significantly improving the sensor's detection sensitivity. Specifically, by introducing KH570 onto the surface of core-shell magnetic porous carbon material Fe3O4@PCS, and using Fe3O4@PCS as a carrier, imprinted polymer materials are prepared. This allows the imprinted polymer materials to be rapidly separated from complex systems under the influence of an external magnetic field, effectively simplifying the preparation process and improving efficiency. Furthermore, compared to electropolymerization, free radical polymerization offers greater monomer diversity and design flexibility. The surface molecular imprinting technology used to prepare molecularly imprinted polymers on the surface of magnetic porous carbon material Fe3O4@PCS results in surface-imprinted polymers with advantages such as easy template molecule removal, uniform distribution of recognition sites, and fast mass transfer rates. The electrochemical sensor prepared in this invention features easy separation and recovery, high recognition efficiency, and a short detection cycle, exhibiting good selectivity, anti-interference ability, and stability against PFOA.

[0035] Furthermore, using the F127-TMB soft template method, a melamine-formaldehyde MF resin shell was prepared on the outside of Fe3O4-NH2 magnetic nanoparticles to coat the surface of Fe3O4 magnetic nanoparticles with a porous carbon layer, which significantly enhanced the stability of Fe3O4 magnetic nanoparticles. Simultaneously, thanks to the high degree of graphitization and abundant pore structure of the porous carbon layer, it not only possesses excellent electron transport capabilities but also provides abundant imprinting sites, thereby improving the detection sensitivity of the sensor. In particular, the porous carbon material prepared using formaldehyde and melamine as carbon and nitrogen sources has a high nitrogen content, which improves the catalytic activity and surface activity of the porous carbon material.

[0036] Furthermore, Co3O4 material was obtained by carbonizing ZIF-67MOF material. The graphitization of carbon during the carbonization process significantly improved the electrical conductivity of the prepared material. By loading Ag nanoparticles onto Co3O4 material, the electrical signal response of the sensor can be further enhanced. Attached Figure Description

[0037] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0038] Figure 1 A schematic diagram illustrating the fabrication process of the molecularly imprinted electrochemical sensor based on magnetic porous carbon materials provided by this invention;

[0039] Figure 2 Transmission electron microscope (TEM) images of Fe3O4@MF, Fe3O4@PCS, and Fe3O4@mSiO2@MIP from Example 1; wherein, Figure 2 a is a transmission electron microscope image of Fe3O4@MF from Example 1. Figure 2 b is a transmission electron microscope image of Fe3O4@PCS in Example 1. Figure 2 c is a transmission electron microscope image of Fe3O4@mSiO2@MIP in Example 1;

[0040] Figure 3 These are scanning electron microscope images of the ZIF-67MOF material and the Co3O4@Ag composite material from Example 1; wherein, Figure 3 a is a scanning electron microscope image of the ZIF-67MOF material in Example 1. Figure 3 b is a scanning electron microscope image of the Co3O4@Ag composite material;

[0041] Figure 4 The infrared spectra of Fe3O4-NH2 magnetic nanoparticles, Fe3O4@MF, Fe3O4@PCS, Fe3O4@PCS-KH570, and Fe3O4@PCS@MIP in Example 1 are shown.

[0042] Figure 5 This is an X-ray diffraction pattern; among which, Figure 5 a is the X-ray diffraction pattern of the ZIF-67MOF material, Co3O4 material and Co3O4@Ag composite material in Example 1; Figure 5 b is the X-ray diffraction pattern of Fe3O4-NH2 magnetic nanoparticles, Fe3O4@MF and Fe3O4@PCS@MIP prepared in Example 1;

[0043] Figure 6 Cyclic voltammetry and impedance plots for electrodes modified with different materials are shown; among them, Figure 6 a represents the cyclic voltammetry curves for GCE, ZIF-67 / GCE, Co3O4 / GCE, Co3O4@Ag / GCE, Fe3O4@PCS / Co3O4@Ag / GCE, and Fe3O4@PCS@MIP / Co3O4@Ag / GCE. Figure 6 b is the sum Figure 6 Impedance spectrum corresponding to the cyclic voltammetry curve in section a; Figure 6 c represents the cyclic voltammetry curves of Fe3O4@PCS@MIP / Co3O4@Ag / GCE before PFOA adsorption, Fe3O4@PCS@MIP / Co3O4@Ag / GCE after PFOA adsorption, and Fe3O4@PCS@MIP / Co3O4@Ag / GCE. Figure 6 d is the sum Figure 6 The impedance spectrum corresponding to the cyclic voltammetry curve in c;

[0044] Figure 7 The image shows a square-wave voltammogram of a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials; where, Figure 7 a is the square wave voltammogram of the molecularly imprinted electrochemical sensor based on magnetic porous carbon material prepared in Example 1 under different concentrations of perfluorooctanoic acid; Figure 7 b is Figure 7 a. Linear relationship between current and perfluorooctanoic acid concentration of the electrochemical sensor Fe3O4@PCS@MIP / Co3O4@Ag / GCE;

[0045] Figure 8 The graph shows the results of selectivity and anti-interference tests for different electrochemical sensors; among them, Figure 8Figure 1 shows the selectivity test results of the electrochemical sensors Fe3O4@PCS@MIP / Co3O4@Ag / GCE and Fe3O4@PCS@NIP / Co3O4@Ag / GCE. Figure 8 b represents the anti-interference test results of the Fe3O4@PCS@MIP / Co3O4@Ag / GCE sensor. Detailed Implementation

[0046] To make the technical problems, technical solutions, and beneficial effects solved by this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0047] This invention provides a method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials, comprising: preparing a core-shell structured magnetic porous carbon material Fe3O4@PCS; introducing KH570 onto the surface of the core-shell structured magnetic porous carbon material Fe3O4@PCS to obtain KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570; performing a free radical polymerization reaction on the KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570 to obtain a magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP; and modifying a composite material of the magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP and Co3O4@Ag onto a predetermined electrode surface to obtain a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials.

[0048] Specifically, the preparation method of the molecularly imprinted electrochemical sensor based on magnetic porous carbon materials is as follows: Figure 1 As shown, it includes the following steps:

[0049] Step 1: Prepare Fe3O4-NH2 magnetic nanoparticles using a solvothermal method; specifically, prepare Fe3O4 magnetic nanoparticles using a solvothermal method, and modify the Fe3O4 magnetic nanoparticles with APTES to obtain Fe3O4-NH2 magnetic nanoparticles.

[0050] More specifically, the steps are as follows:

[0051] Ferric chloride, sodium citrate, and anhydrous sodium acetate were dissolved in ethylene glycol, ultrasonically stirred, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene for reaction to obtain the reaction product. The reaction product was magnetically separated, washed, and vacuum dried to obtain Fe3O4 nanoparticles. The Fe3O4 nanoparticles were ultrasonically dispersed in a mixed solution of ethanol and deionized water, and APTES was added and stirred for reaction. After the reaction was completed, magnetic separation, washing, and vacuum drying were performed to obtain Fe3O4-NH2 magnetic nanoparticles.

[0052] Step 2: Using Fe3O4-NH2 magnetic nanoparticles as the magnetic core, a melamine-formaldehyde MF resin shell is prepared on the outside of the Fe3O4-NH2 magnetic nanoparticles using the F127-TMB soft template method to obtain Fe3O4@MF; Fe3O4@MF is then carbonized to obtain Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure.

[0053] The specific process and steps are as follows:

[0054] F127 was dissolved in deionized water, and TMB was added and magnetically stirred to obtain solution A. Fe3O4-NH2 magnetic nanoparticles were ultrasonically dispersed in deionized water, and melamine, formaldehyde solution, and NaOH aqueous solution were added and mechanically stirred to obtain solution B. Solution A was added to solution B, followed by acetic acid, and the reaction was carried out under mechanical stirring. After the reaction was completed, Fe3O4@MF was obtained by magnetic separation, washing, and vacuum drying. Fe3O4@MF was calcined at high temperature in a tube furnace filled with N2 atmosphere to obtain Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure.

[0055] Step 3: The magnetic porous carbon material Fe3O4@PCS with a core-shell structure is ultrasonically dispersed in an ethanol solution, KH570 is added and stirred evenly, and the reaction is carried out by water bath heating. After the reaction, it is magnetically separated, washed and vacuum dried to obtain the KH570 modified magnetic porous carbon material Fe3O4@PCS-KH570.

[0056] Step 4: Using KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570 as a polymerization carrier, template molecules, functional monomers, crosslinking agents, and initiators are added to carry out free radical polymerization to obtain the polymerization product. The template molecules in the polymerization product are removed by Soxhlet extraction to obtain the magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP. The template molecule is perfluorooctanoic acid (PFOA), the functional monomers are acrylamide (AAM) and 2-trifluoromethylacrylic acid (TFMAA), the crosslinking agent is ethylene glycol dimethacrylate (EGDMA), and the initiator is azobisisobutyronitrile (AIBN).

[0057] Step 5: Dissolve Co(NO3)2·6H2O in methanol to obtain a methanol solution of Co(NO3)2·6H2O; dissolve 2-methylimidazole in methanol to obtain a methanol solution of 2-methylimidazole; mix the methanol solution of Co(NO3)2·6H2O and the methanol solution of 2-methylimidazole and stir, then let it stand for aging; after aging, centrifuge, wash and vacuum dry to obtain ZIF-67MOF material; place the ZIF-67MOF material in a tube furnace and calcine it under a nitrogen atmosphere to obtain Co3O4 material; ultrasonically disperse the Co3O4 material in deionized water, add AgNO3 aqueous solution and mechanically stir, then add NaBH4 solution dropwise under an ice-water bath to react, after the reaction is completed, centrifuge, wash and vacuum dry to obtain Co3O4@Ag composite material.

[0058] Step 6: Disperse the Co3O4@Ag composite material in ultrapure water to obtain dispersion system A; disperse the magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP in ultrapure water to obtain dispersion system B; sequentially drop-coat dispersion system A and dispersion system B onto the surface of a preset electrode, and after drying, obtain a molecularly imprinted electrochemical sensor based on magnetic porous carbon material; preferably, the preset electrode is a pretreated glassy carbon electrode (GCE), and the pretreatment process of the glassy carbon electrode includes polishing, cleaning and drying of the glassy carbon electrode; therefore, the molecularly imprinted electrochemical sensor based on magnetic porous carbon material is denoted as Fe3O4@PCS@MIP / Co3O4@Ag / GCE.

[0059] Preparation principle:

[0060] The method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials described in this invention uses Fe3O4-NH2 magnetic nanoparticles prepared by a solvothermal method as the magnetic core, so that the imprinted material can be separated from the medium during preparation and use. A melamine-formaldehyde (MF) resin shell is prepared on the outside of the Fe3O4-NH2 magnetic nanoparticles using the F127-TMB soft template method. Coating the surface of the magnetic core with a porous carbon layer not only effectively prevents the magnetic core from being oxidized or corroded, but also provides abundant imprinting sites, effectively improving mass transfer efficiency. The elution of template molecules and the adsorption of target molecules ensure rapid binding of target molecules, thereby improving the detection sensitivity of the constructed sensor. KH570 was modified onto the surface of Fe3O4@PCS, a core-shell magnetic porous carbon material, and a molecularly imprinted layer was prepared via free radical polymerization to obtain the magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP. Due to the presence of the magnetic core, the products can be separated during material preparation using an external magnetic field, significantly simplifying the preparation process. Simultaneously, the mesoporous carbon layer can provide a richer number of imprinting sites. This improves the detection sensitivity of the electrochemical sensor. Specifically, ZIF-67MOF material is calcined at high temperature to obtain Co3O4 material, which significantly enhances the conductivity of the prepared material through carbon graphitization during carbonization. Ag nanoparticles are loaded onto the Co3O4 material to further improve the conductivity of the electrode modification material. A magnetic surface molecularly imprinted polymer (Fe3O4@PCS@MIP) is obtained by free radical polymerization on the surface of KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570. This allows the imprinted polymer material to be rapidly separated from the complex system under the influence of an external magnetic field, effectively simplifying the preparation process and improving the material preparation efficiency. The magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP (after template molecule removal) and the electrode modification Co3O4@Ag composite material are respectively drop-coated onto the surface of a glassy carbon electrode. Based on the rich pore structure of the porous carrier, the prepared imprinted polymer has abundant recognition sites, ultimately improving the detection sensitivity of the prepared sensor and obtaining an electrochemical sensor capable of detecting perfluorooctanoic acid (PFOA).

[0061] The molecularly imprinted electrochemical sensor based on magnetic porous carbon materials prepared in this invention has an imprinted layer distributed on the surface of a solid support (Fe3O4@PCS), making the imprinted sites easily accessible and enabling rapid recognition of template molecules. The presence of imprinted cavities allows perfluorooctanoic acid (PFOA) to rapidly bind to the recognition sites, achieving specific recognition of PFOA. When the imprinted cavities are filled with PFOA, electron transfer is hindered, and the change in current can be monitored in real time. Furthermore, due to the poor conductivity of the polymer, the channel between the electrode surface and the detection solution is blocked after the imprinted cavities are filled, thus hindering electron transfer. Therefore, the molecularly imprinted electrochemical sensor based on magnetic porous carbon materials can be used for the identification and detection of PFOA in environmental systems.

[0062] In this invention, Fe3O4-NH2 magnetic nanoparticles were used as the magnetic core, and an MF shell was prepared on the outside of the magnetic core using the F127-TMB soft template method to obtain Fe3O4@MF. Fe3O4@MF was then subjected to high-temperature carbonization to obtain Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure. By grafting KH570 onto the surface of Fe3O4@PCS, polymerizable double bonds were successfully introduced into the support. Using PFOA as the template molecule and AAM and TFMAA as functional monomers, M was prepared by free radical polymerization on the support surface. An IP layer was formed to obtain a Fe3O4@PCS@MIP composite material. Co3O4 material was obtained by high-temperature calcination of ZIF-67MOF material under a nitrogen atmosphere. To further improve the conductivity of the electrode modification material, Ag nanoparticles were loaded onto the Co3O4 material. The Co3O4@Ag composite material and Fe3O4@PCS@MIP were then drop-coated onto a GCE to construct a molecularly imprinted electrochemical sensor for PFOA detection. This sensor exhibits good selectivity, anti-interference ability, and stability for PFOA, and has broad application prospects.

[0063] Example 1

[0064] This embodiment 1 provides a method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials, including the following steps:

[0065] Step 1: Dissolve 2.6 g of anhydrous ferric chloride, 1.0 g of sodium citrate, and 4.0 g of anhydrous sodium acetate in 80 mL of ethylene glycol. After ultrasonic stirring for 30 min, transfer the solution to a stainless steel autoclave lined with polytetrafluoroethylene (PTFE). React at 200 °C for 10 h to obtain the reaction product. Magnetic separation of the reaction product is performed using an external magnetic field. The product is washed sequentially with deionized water and ethanol, and then vacuum dried at 60 °C for 12 h to obtain Fe3O4 nanoparticles. 0.25 g of Fe3O4 nanoparticles are ultrasonically dispersed in a mixed solution of 10 mL of ethanol and deionized water and mechanically stirred for 30 min. Then, 1.01 mL of APTES is added and stirred for 2 h under a 40 °C water bath. After the reaction, cool to room temperature for magnetic separation. Wash three times with deionized water and ethanol respectively, and then vacuum dried to obtain Fe3O4-NH2 magnetic nanoparticles. The volume ratio of ethanol to deionized water in the mixed solution is 1:1.

[0066] Step 2: Dissolve 3.6g of F127 in 60mL of deionized water, add 7.2g of TMB, and magnetically stir at 1000rpm for 6h to obtain solution A; ultrasonically disperse 0.15g of Fe3O4-NH2 magnetic nanoparticles in 180mL of deionized water, add 2.2704g of melamine, 1.9896mL of formaldehyde solution, and 0.3mL of NaOH aqueous solution, and mechanically stir in an oil bath at 100℃ for 0.5h to obtain solution B; wherein the concentration of formaldehyde solution is 37wt%, and the concentration of NaOH aqueous solution is... 0.1M; Solution A was added to solution B and reacted at 100℃ for 2h, followed by the addition of 0.9mL acetic acid and mechanical stirring at 120rpm for 6h. After the reaction was completed, the mixture was cooled to room temperature for magnetic separation. After washing three times with deionized water and ethanol, the mixture was vacuum dried at 60℃ for 12h to obtain Fe3O4@MF. Fe3O4@MF was preheated at 350℃ for 3h in a tube furnace filled with N2 atmosphere at a heating rate of 3℃ / min, and then calcined at 700℃ for 2h to obtain Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure.

[0067] Step 3: 50 mg of core-shell structured magnetic porous carbon material Fe3O4@PCS was ultrasonically dispersed in a mixed solution of 7.5 mL ethanol and 2.5 mL deionized water. 0.17 mL of KH570 was added and mechanically stirred for 30 min. The mixture was heated in a 65 °C water bath for 2 h. After the reaction, the mixture was magnetically separated, washed three times with deionized water and ethanol, and then vacuum dried at 60 °C for 12 h to obtain KH570 modified magnetic porous carbon material Fe3O4@PCS-KH570.

[0068] Step 4: 20 mg of KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570 was dispersed in 30 mL of acetone and stirred ultrasonically for 0.5 h. Then, 41.4 mg of PFOA, 14.22 mg of AAM, and 28 mg of TFMAA were added and mechanically stirred for 6 h for prepolymerization. Subsequently, 0.01 g of AIBN and 0.376 mL of EGDMA were added under a N2 atmosphere, and the reaction was carried out in a 60 °C water bath for 12 h. After the reaction was completed, the mixture was cooled to room temperature and subjected to magnetic separation. After separation, the product was washed three times with acetone and ethanol, and dried under vacuum at 60°C for 12 h to obtain the polymerization product. The polymerization product was placed in a filter paper bag and extracted with methanol and acetic acid in a volume ratio of 6:1 at 120°C for 72 h to remove the template molecules in the polymerization product, thus obtaining the magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP. It should be noted that Fe3O4@PCS@NIP was prepared without the addition of PFOA for performance comparison.

[0069] Step 5: Dissolve 1.4 g of Co(NO3)2·6H2O in 120 mL of methanol to obtain a methanol solution of Co(NO3)2·6H2O; dissolve 2.56 g of 2-methylimidazole in 120 mL of methanol to obtain a methanol solution of 2-methylimidazole; mix the methanol solutions of Co(NO3)2·6H2O and 2-methylimidazole and stir for 30 min, then let stand for aging for 24 h; after aging, centrifuge at 9000 rpm for 10 min, wash the precipitate three times with ethanol, and dry under vacuum at 60 °C for 12 h to obtain ZIF-67MOF material; place the ZIF-67MOF material in a tube furnace, heat it at a heating rate of 5 °C / min in a tube furnace filled with N2 atmosphere, and calcine it at 700 °C for 2 h to obtain Co3O4 material; 15 mg of Co3O4 material was ultrasonically dispersed in 10 mL of deionized water under mechanical stirring for 30 min to obtain a Co3O4 dispersion. 3 mL of AgNO3 was dissolved in 3 mL of deionized water to obtain an AgNO3 aqueous solution. The AgNO3 aqueous solution was added to the Co3O4 dispersion, and stirring was continued for 30 min to obtain a mixed dispersion. 6.68 mg of NaBH4 was dissolved in 2 mL of deionized water to obtain a NaBH4 solution. The mixed dispersion was placed in an ice-water bath, and the NaBH4 solution was added dropwise at a rate of 4 s / drop. After the addition was completed, the mixture was reacted in an ice-water bath for 30 min. After the reaction was completed, the mixture was centrifuged at 10000 rpm for 10 min, the precipitate was washed with deionized water, and the mixture was vacuum dried at 60 °C for 12 h to obtain the Co3O4@Ag composite material.

[0070] Step 6: Polish the GCE with 0.5μm and 0.05μm alumina slurries respectively; clean the polished GCE with ultrapure water and anhydrous ethanol under ultrasonication, and then dry it with nitrogen to obtain a pretreated GCE; disperse 1mg of Co3O4@Ag composite material in ultrapure water, and obtain a Co3O4@Ag dispersion with a concentration of 1mg / mL after ultrasonication; disperse 1mg of magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP in ultrapure water, and obtain a Fe3O4@PCS@MIP dispersion with a concentration of 1mg / mL after ultrasonication; drop-coat 10μL of Co3O4@Ag dispersion and 5μL of Fe3O4@PCS@MIP dispersion onto the pretreated GCE and allow it to dry naturally at room temperature to obtain a molecularly imprinted electrochemical sensor based on magnetic porous carbon material, denoted as Fe3O4@PCS@MIP / Co3O4@Ag / GCE.

[0071] Performance testing experiments:

[0072] A 3 mm diameter glassy carbon electrode was used as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum wire as the counter electrode. SWV tests were performed in 0.1 M PBS and ethanol (V / V = 9 / 1), and 5 mM [Fe(CN)6] solutions. 3- / 4- PFOA was determined in a phosphate buffer solution of 0.1 MkCl; the test potential range was -0.10 to 0.40 V, the amplitude was set to 25 mV, and the frequency was set to 15 Hz.

[0073] Performance test results explanation:

[0074] As attached Figure 2 As shown, attached Figure 2 Transmission electron microscope (TEM) images of Fe3O4@MF, Fe3O4@PCS, and Fe3O4@mSiO2@MIP from Example 1 are provided; among them, Figure 2 a is a transmission electron microscope image of Fe3O4@MF from Example 1. Figure 2 b is a transmission electron microscope image of Fe3O4@PCS in Example 1. Figure 2 c is a transmission electron microscope image of Fe3O4@mSiO2@MIP from Example 1; from Figure 2 As can be seen from a, Fe3O4@MF has a monodisperse spherical morphology, exhibiting a regular and uniform porous structure with a particle size of approximately 350 nm; after carbonization of Fe3O4@MF in a N2 atmosphere at 700℃, it becomes... Figure 2b. It can be observed that the Fe3O4@PCS nanospheres retain their monodisperse spherical morphology without structural deformation. Due to the pyrolysis of the Fe3O4@MF nanospheres at high temperature, the particle size of the resulting Fe3O4@PCS nanospheres shrinks to approximately 230 nm, with a volume shrinkage rate of approximately 34%. After the polymerization reaction, from... Figure 2 As shown in Figure c, the Fe3O4@PCS surface is coated with a polymer film, confirming the successful preparation of Fe3O4@PCS@MIP.

[0075] As attached Figure 3 As shown, attached Figure 3 Scanning electron microscope images of the ZIF-67MOF material and the Co3O4@Ag composite material in Example 1 are given; wherein, Figure 3 a is a scanning electron microscope image of the ZIF-67MOF material in Example 1. Figure 3 b is a scanning electron microscope image of the Co3O4@Ag composite material; from Figure 3 As can be seen, the prepared ZIF-67MOF material exhibits a smooth rhombic polyhedral morphology; from Figure 3 As can be seen from b, after high-temperature carbonization, the Co3O4 material exhibits a rough surface with pores. Although the size of the material is reduced, it still retains the polyhedral shape of the original ZIF-67MOF material. After loading Ag nanoparticles onto the Co3O4 material, the Ag nanospheres are uniformly distributed on the surface of the Co3O4 material. The combination of Ag and Co3O4 material does not affect the polyhedral structure of the Co3O4 material, which also confirms the successful preparation of the Co3O4@Ag composite material.

[0076] As attached Figure 4 As shown, attached Figure 4 The infrared spectra of Fe3O4-NH2 magnetic nanoparticles, Fe3O4@MF, Fe3O4@PCS, Fe3O4@PCS-KH570, and Fe3O4@PCS@MIP from Example 1 are given; Figure 4 As can be seen from the infrared spectrum of Fe3O4-NH2, the 572 cm⁻¹... -1 The absorption peak at 2935 cm⁻¹ can be attributed to the stretching vibration of Fe-O in Fe₃O₄. -1 1000cm -1 and 845cm -1 The three absorption peaks at 1569 cm⁻¹ correspond to the stretching vibrations of CH, Si-O-Si, and Si-O in APTES, respectively, confirming that APTES has been successfully modified onto the surface of Fe₃O₄ nanoparticles. Compared with Fe₃O₄-NH₂, the infrared spectrum of Fe₃O₄@MF shows a higher peak at 1569 cm⁻¹. -1A new strong absorption peak appeared at [value missing], which is due to the C=N vibration of melamine, confirming the successful coating of the MF layer on Fe3O4 nanoparticles; after high-temperature carbonization, the infrared spectrum of Fe3O4@PCS includes [value missing] 1569 cm⁻¹. -1 The infrared signals of organic residues, including the C=N characteristic peak, almost completely disappeared; in the 1200-1700 cm⁻¹ range... -1 and 3200-3500cm -1 A weak absorption peak appeared at 1099 cm⁻¹; the above results indicate that the MF layer has been transformed into a nitrogen-rich carbon material after carbonization; a peak at 1099 cm⁻¹ was observed in the infrared spectrum of Fe₃O₄@PCS-KH570. -1 The absorption peak of Si-O at the 1640 cm⁻¹ confirms that KH570 has been successfully grafted onto the Fe3O4@PCS surface; after polymerization on the Fe3O4@PCS-KH570 support surface, the 1640 cm⁻¹ infrared spectrum of Fe3O4@PCS@MIP shows... -1 The absorption peak appearing in [the sample] is attributed to the characteristic peak of C=N in AAM. At 1728 cm⁻¹... -1 The absorption peak at 1158 cm⁻¹ can be attributed to the stretching vibration of C=O in TFMAA; -1 The characteristic peak at the location corresponds to the symmetric stretching vibration of CO in the crosslinking agent EGDMA, confirming the successful synthesis of the MIP layer.

[0077] As attached Figure 5 As shown, Figure 5 The X-ray diffraction pattern is shown below. Figure 5 a is the X-ray diffraction pattern of the ZIF-67MOF material, Co3O4 material and Co3O4@Ag composite material in Example 1; Figure 5 b is the X-ray diffraction pattern of the Fe3O4-NH2 magnetic nanoparticles, Fe3O4@MF, and Fe3O4@PCS@MIP prepared in Example 1; from Figure 5As can be seen, the XRD pattern of ZIF-67MOF material has sharp and narrow peaks, indicating that the prepared ZIF-67MOF material has high crystallinity. Furthermore, the diffraction peaks at 10.4°, 12.7°, 14.7°, 16.5°, 18.1°, 22.2°, 24.4°, 25.6°, 26.7°, 29.7°, 30.6°, and 32.4° correspond to the (002), (112), (022), (013), (222), (114), (233), (224), (134), (044), (334), (244), and (235) crystal planes, confirming the high crystallinity of ZIF-67MOF. The successful synthesis of F material; after ZIF-67MOF material was carbonized into Co3O4 material, the characteristic peaks of ZIF-67MOF material disappeared, indicating that the crystal structure of ZIF-67MOF material changed; new (400) and (422) crystal planes appeared, confirming the successful synthesis of Co3O4 material; after loading Ag nanoparticles onto Co3O4 material, characteristic diffraction peaks of Ag nanoparticles appeared at 38.13°, corresponding to the (111) crystal plane, confirming the successful preparation of Ag nanoparticles; and the characteristic peaks of Co3O4 material did not change; the results show that Ag nanoparticles successfully combined with Co3O4 material, and Ag nanoparticles had almost no effect on the crystal structure of Co3O4 material; from Figure 5 b shows that the diffraction peaks at 30.2°, 35.5°, 43.2°, 53.5°, 57.2° and 62.7° correspond to the (220), (311), (400), (422), (511) and (440) crystal planes, confirming the successful preparation of Fe3O4. Furthermore, after coating Fe3O4 with a porous carbon layer and a MIP layer, the diffraction peaks of Fe3O4 can still be observed in the XRD patterns of Fe3O4@PCS and Fe3O4@PCS@MIP, indicating that the coating did not change the crystal structure of Fe3O4.

[0078] As attached Figure 6 As shown, attached Figure 6 Cyclic voltammetry and impedance plots of electrodes modified with different materials are presented; among them, Figure 6 a represents the cyclic voltammetry curves for GCE, ZIF-67 / GCE, Co3O4 / GCE, Co3O4@Ag / GCE, Fe3O4@PCS / Co3O4@Ag / GCE, and Fe3O4@PCS@MIP / Co3O4@Ag / GCE. Figure 6 b is the sum Figure 6 Impedance spectrum corresponding to the cyclic voltammetry curve in section a; Figure 6c represents the cyclic voltammetry curves of Fe3O4@PCS@MIP / Co3O4@Ag / GCE before PFOA adsorption, Fe3O4@PCS@MIP / Co3O4@Ag / GCE after PFOA adsorption, and Fe3O4@PCS@MIP / Co3O4@Ag / GCE. Figure 6 d is the sum Figure 6 The impedance spectrum corresponding to the cyclic voltammetry curve in c; from Figure 6 As shown in Figure a, the bare electrode GCE exhibits a pair of distinct redox peaks; the peak current of the ZIF-67 modified electrode is significantly lower than that of the bare GCE, indicating that ZIF-67 inhibits electron transfer; when ZIF-67 is calcined at high temperature to form Co3O4, the redox peak current intensity of Co3O4 / GCE increases significantly, indicating that the carbonization process significantly improves the conductivity of the prepared material, which can be attributed to the graphitization of carbon during the carbonization process; simultaneously, the doping of porous cubic carbon with Co nanoparticles improves the conductivity of electron transfer; the current response of Co3O4@Ag / GCE is higher than that of Co3O4 / GCE, thanks to the excellent conductivity of Ag and the interaction between Ag and GCE. The synergistic effect of Co3O4; after modifying the electrode surface with Co3O4@Ag and Fe3O4@PCS respectively, the peak current of Fe3O4@PCS / Co3O4@Ag / GCE reached its maximum; the nitrogen-containing porous carbon spheres formed around Fe3O4 after high-temperature carbonization have a high degree of graphitization and rich pore structure, with good electron transport ability, significantly improving the conductivity of the material; after coating the carrier surface with a MIP layer, the current response of Fe3O4@PCS@MIP / Co3O4@Ag / GCE decreased because the non-conductive MIP film drop-coated on the GCE surface increased the resistance, resulting in a decrease in current; from Figure 6 The EIS plot of b yielded results consistent with the CV test; furthermore, the electrochemical performance of MIP before and after PFOA adsorption and that of NIP were investigated using CV and EIS, with results as follows: Figure 6 As shown in c and 6d; when Fe3O4@PCS@MIP / Co3O4@Ag / GCE is incubated in PFOA solution, the redox peak current intensity weakens because PFOA enters the MIP cavity and combines with the recognition site; when the NIP-coated composite material Fe3O4@PCS@NIP and Co3O4@Ag are used to modify the electrode together, R ct The increase in value and the significantly lower peak current compared to Fe3O4@PCS@MIP / Co3O4@Ag / GCE is because the template molecules in the MIP are removed, forming a three-dimensional cavity. The presence of this cavity increases the electron transfer rate and accelerates the redox reaction. In contrast, the NIP lacks the formation of imprinted cavities, thus hindering the entry of the redox probe. The EIS and CV test results are consistent.

[0079] Example 2

[0080] This embodiment 2 is basically the same as the steps and principles of embodiment 1 above, except that:

[0081] Perfluorooctanoic acid (PFOA) was detected using phosphate buffer solutions with different pH values ​​via the electrochemical sensor to determine the optimal pH value of the phosphate buffer solution.

[0082] Specifically, 1 mol / L KCl and 5 mmol / L [Fe(CN)6] were used. 3- / 4- A phosphate buffer solution was prepared, with the following pH values ​​designed sequentially: pH = 2.0, pH = 3.0, pH = 4.0, pH = 5.0, pH = 6.0, pH = 7.0, and pH = 8.0. The current response of the sensor in the pH range of 2.0–8.0 was investigated using square wave voltammetry (SWV) within the range of -0.10–0.40 V. Within the pH range of 2.0–6.0, increasing the pH value increased the peak current, reaching its maximum at pH 6.0. The peak current decreased significantly at pH 7.0 and 8.0. Therefore, pH = 6.0 was selected as the optimal pH condition.

[0083] Example 3

[0084] This embodiment 3 is basically the same as the steps and principles of embodiment 1 above, except that:

[0085] The amount of Co3O4@Ag dispersion to be dropped.

[0086] Specifically, the dropper volumes of the 1 mg / mL Co3O4@Ag dispersion were 2 μL, 4 μL, 6 μL, 8 μL, 10 μL, 12 μL, and 14 μL. As the dropper volume increased, the sensor's current response gradually increased, but after reaching 10 μL, the peak current change became gradual with further increases in dropper volume. The electrode surface has limited carrying capacity; excessive dropper volume not only fails to achieve a higher current response but also causes excess modifying material to detach from the electrode surface, thus contaminating the electrolyte. Therefore, the optimal dropper volume for Co3O4@Ag material is 10 μL.

[0087] Example 4

[0088] This embodiment 4 is basically the same as the steps and principles of embodiment 1 above, except that:

[0089] Incubation time for perfluorooctanoic acid.

[0090] Specifically, as the incubation time increases, the difference between the current at a fixed time and the current before incubation gradually increases, reaching its maximum at 350 s. With further extension of the incubation time, the current difference remains almost constant, because the adsorption of PFOA by MIP has reached equilibrium. Therefore, the optimal incubation time is 350 s.

[0091] Test Example 1

[0092] Test Example 1 uses the electrochemical sensor prepared in Example 1. During electrochemical detection, the concentration of perfluorooctanoic acid is changed to test the sensitivity of the sensor.

[0093] As attached Figure 7 As shown, attached Figure 7 Square-wave voltammetry of a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials is presented; among which, Figure 7 a is the square wave voltammogram of the molecularly imprinted electrochemical sensor based on magnetic porous carbon material prepared in Example 1 under different concentrations of perfluorooctanoic acid; Figure 7 b is Figure 7 a. Linear relationship between current and perfluorooctanoic acid (PFOA) concentration using the prepared Fe3O4@PCS@MIP / Co3O4@Ag / GCE electrochemical sensor. d. Detection of PFOA and [Fe(CN)6] using the prepared Fe3O4@PCS@MIP / Co3O4@Ag / GCE sensor. 3- / 4- As a redox probe; from Figure 7 As can be seen from graph a, the peak SWV current gradually decreases with increasing PFOA concentration, and there are two segments of good linear relationship between PFOA concentration and the decrease in peak SWV current, such as... Figure 7 As shown in b; within the concentration range of 0.05-1 μM, the linear equation for the decrease in SWV peak current with respect to PFOA concentration is ΔI(μA)=13.1649C(μM)+8.0654(R) 2 =0.9933); When the PFOA concentration is between 1-50 μM, the linear equation for the decrease in SWV peak current with respect to PFOA concentration is ΔI(μA) = 1.3485C(μM) + 21.7349(R) 2 =0.9942), and the limit of detection (LOD) is 0.001 μM; thus, the prepared molecularly imprinted electrochemical sensor based on magnetic porous carbon material has a wide detection range and a low detection limit for the quantitative determination of PFOA.

[0094] Test Example 2

[0095] This test example 2 uses the electrochemical sensor prepared in Example 1, and employs structural analogs of perfluorooctanoic acid (PFOA), such as perfluoroheptanoic acid (PFHA), perfluorodecanoic acid (PHDA), and perfluorononanoic acid (PFNA), to study the selectivity of the imprinted polymer; it also uses PFOA structural analogs and common interfering ion types such as Ca2+ in actual sample detection. 2+ Cu 2+ and Zn 2+ To study the anti-interference properties of imprinted polymers.

[0096] As attached Figure 8 As shown, attached Figure 8 The results of selectivity and anti-interference tests for different electrochemical sensors are shown in the figure; among them, Figure 8 Figure 1 shows the selectivity test results of the electrochemical sensors Fe3O4@PCS@MIP / Co3O4@Ag / GCE and Fe3O4@PCS@NIP / Co3O4@Ag / GCE. Figure 8 b represents the anti-interference test results of the Fe3O4@PCS@MIP / Co3O4@Ag / GCE sensor; from the attached... Figure 8 As shown in Figure a, the MIP sensor exhibits the highest current response to PFOA, significantly higher than that of the NIP sensor, indicating good selectivity for PFOA and its ability to specifically detect it. To further explore the anti-interference capability of the MIP sensor, SWV tests were performed on the sensor in the presence of 10 μM FOA and six different interfering substances at 10 times the concentration. Among these, the molecular structures of the interfering substances PFHA, PHDA, and PFNA are similar to those of PFOA, while Ca... 2+ Cu 2+ and Zn 2+ Ions are common types of interfering ions in actual sample detection, such as Figure 8 As shown in b; from the appendix Figure 8 As can be seen from b, the influence of interfering substances on the sensor's specific recognition is negligible, indicating that the sensor has good anti-interference capabilities.

[0097] The present invention describes a method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials. The method utilizes Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure, as a carrier for imprinting polymerization to prepare a magnetic surface molecularly imprinted polymer. The prepared imprinted polymer can specifically recognize perfluorooctanoic acid (PFOA) in a short time. The presence of the magnetic core allows the imprinted polymer to separate rapidly under an applied magnetic field, and the porous carbon layer structure of PCS increases the binding sites of the imprinted material. By modifying the electrode with the magnetic surface molecularly imprinted polymer and the Co3O4@Ag composite material, once the imprinted cavity is filled with PFOA molecules, the redox process of the probe ions is hindered, resulting in fluctuations in the current response. Combining the high selectivity of the magnetic surface molecularly imprinted polymer with the high sensitivity of the electrochemical test, this sensor is expected to achieve the identification and detection of PFOA in complex environments in practical applications.

[0098] This invention overcomes the shortcomings of poor selectivity in previous detection methods by employing molecular imprinting technology, and also overcomes the limitation of traditional detection techniques in real-time monitoring by utilizing electrochemical sensors. The prepared magnetic surface molecularly imprinted polymer is used as a recognition element, and its specific recognition performance of template molecules affects the transfer of electrons at the electrode. Simultaneously, an electrochemical workstation is used for experimental processing and data recording, thereby achieving real-time detection of template molecules. Furthermore, due to the low cost and portability of the electrochemical workstation, real-time trace detection in the environmental field can be achieved, overcoming the shortcomings of complex and time-consuming pretreatment in traditional detection methods.

[0099] The above embodiments are merely one of the implementation methods for achieving the technical solution of the present invention. The scope of protection claimed by the present invention is not limited to this embodiment, but also includes any variations, substitutions and other implementation methods that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention.

Claims

1. A method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials, characterized in that, include: Preparation of Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure; KH570 was introduced onto the surface of the magnetic porous carbon material Fe3O4@PCS with a core-shell structure to obtain KH570 modified magnetic porous carbon material Fe3O4@PCS-KH570; Free radical polymerization was carried out on the surface of KH570 modified magnetic porous carbon material Fe3O4@PCS-KH570 to obtain magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP; By modifying the surface of a pre-defined electrode with magnetic surface molecularly imprinted polymers Fe3O4@PCS@MIP and Co3O4@Ag composite materials, a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials is obtained.

2. The method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon material according to claim 1, characterized in that, The process for preparing Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure, includes: Fe3O4-NH2 magnetic nanoparticles were prepared using a solvothermal method. Using Fe3O4-NH2 magnetic nanoparticles as the magnetic core, a melamine-formaldehyde MF resin shell was prepared on the outside of the Fe3O4-NH2 magnetic nanoparticles using the F127-TMB soft template method to obtain Fe3O4@MF. Fe3O4@MF was carbonized to obtain Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure.

3. The method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon material according to claim 1, characterized in that, The process of introducing KH570 onto the surface of the core-shell structured magnetic porous carbon material Fe3O4@PCS to obtain KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570 is as follows: Fe3O4@PCS, a magnetic porous carbon material with a core-shell structure, was ultrasonically dispersed in an ethanol solution. KH570 was added and stirred until homogeneous. The mixture was then heated in a water bath to react. After the reaction, the mixture was magnetically separated, washed, and vacuum dried to obtain the KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570.

4. The method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon material according to claim 1, characterized in that, The process of obtaining the magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP by free radical polymerization on the KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570 surface includes: Using KH570-modified magnetic porous carbon material Fe3O4@PCS-KH570 as a polymerization support, template molecules, functional monomers, crosslinking agents and initiators were added to carry out free radical polymerization to obtain the polymerization product. The template molecules in the polymerization product were removed by Soxhlet extraction to obtain the magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP.

5. The method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon material according to claim 4, characterized in that, The template molecule is perfluorooctanoic acid, the functional monomers are acrylamide and 2-trifluoromethacrylic acid, the crosslinking agent is ethylene glycol dimethacrylate, and the initiator is azobisisobutyronitrile.

6. The method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon material according to claim 1, characterized in that, The preparation process of Co3O4@Ag composite material includes: ZIF-67MOF material was calcined under a nitrogen atmosphere to obtain Co3O4 material; Co3O4 material was ultrasonically dispersed in deionized water, AgNO3 aqueous solution was added and mechanically stirred, and then NaBH4 solution was added dropwise under an ice-water bath to carry out the reaction. After the reaction was completed, the Co3O4@Ag composite material was obtained by centrifugation, washing and vacuum drying.

7. The method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon material according to claim 6, characterized in that, The preparation process of ZIF-67MOF material includes: A methanol solution of Co(NO3)2·6H2O and a methanol solution of 2-methylimidazole were mixed and stirred, and then allowed to stand for aging. After aging, the ZIF-67MOF material was obtained by centrifugation, washing and vacuum drying.

8. The method for preparing a molecularly imprinted electrochemical sensor based on magnetic porous carbon material according to claim 1, characterized in that, The process of modifying the surface of a pre-defined electrode with magnetic surface molecularly imprinted polymers Fe3O4@PCS@MIP and Co3O4@Ag composite materials to obtain a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials is as follows: The Co3O4@Ag composite material was dispersed in ultrapure water to obtain dispersion system A; The magnetic surface molecularly imprinted polymer Fe3O4@PCS@MIP was dispersed in ultrapure water to obtain dispersion system B; The dispersion system A and the dispersion system B were sequentially drop-coated onto the surface of a preset electrode, and after drying, a molecularly imprinted electrochemical sensor based on magnetic porous carbon material was obtained.

9. A molecularly imprinted electrochemical sensor based on magnetic porous carbon materials, characterized in that, The molecularly imprinted electrochemical sensor based on magnetic porous carbon material was prepared using the method described in any one of claims 1-8.

10. The application of a molecularly imprinted electrochemical sensor based on magnetic porous carbon materials as described in claim 9, characterized in that, The molecularly imprinted electrochemical sensor based on magnetic porous carbon material is used to identify and detect perfluorooctanoic acid in an environmental system.

Citation Information

Patent Citations

  • Perfluorooctanoic acid anti-interference electrochemical molecular imprinting sensor as well as preparation method and application thereof

    CN118533933A

  • Perfluorooctanoic acid electrochemical sensor based on molecular imprinting and aptamer double recognition as well as construction method and application of perfluorooctanoic acid electrochemical sensor

    CN118671155A

  • Fluorine-philic hydrophobic functional monomer, synthesis method and application thereof, detection electrode and preparation method thereof

    CN119552106A